2012
DOI: 10.1177/0300985812436745
|View full text |Cite
|
Sign up to set email alerts
|

A Forensic Investigation Into the Etiology of Bat Mortality at a Wind Farm: Barotrauma or Traumatic Injury?

Abstract: Migrating bats have increased mortality near moving turbine blades at wind farms. The authors evaluated competing hypotheses of barotrauma and traumatic injury to determine the cause. They first examined the utility of lungs from salvaged bat carcasses for histopathologic diagnosis of barotrauma and studied laboratory mice as a model system. Postmortem time, environmental temperature, and freezing of carcasses all affected the development of vascular congestion, hemorrhage, and edema. These common tissue artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Quantifi cation of bat mortality is based on dead bats numbers by turbine by year and dead bat numbers by energy produced (Cryan & Barclay 2009;Kuvlesky et al 2007). Previous articles reported key diagnostic features from dead bats found in wind energy facilities (Rollins et al 2012;Baerwald et al 2008). Pulmonary damage and signs of traumatic injury have been the most frequent lesions found in dead bats collected near turbines (Rollins et al 2012;Baerwald et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifi cation of bat mortality is based on dead bats numbers by turbine by year and dead bat numbers by energy produced (Cryan & Barclay 2009;Kuvlesky et al 2007). Previous articles reported key diagnostic features from dead bats found in wind energy facilities (Rollins et al 2012;Baerwald et al 2008). Pulmonary damage and signs of traumatic injury have been the most frequent lesions found in dead bats collected near turbines (Rollins et al 2012;Baerwald et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date have indicated that bat fatalities occur as a result of traumatic injury following collisions with moving turbines and possibly from barotrauma (Baerwald et al 2008), although the incidence of barotrauma has been recently queried, with collisions thought to be the primary cause of fatality (Grodskey et al 2011;Rollins et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While preliminary research [4], [10] suggested that barotrauma was responsible for a significant fraction of turbine-related deaths, more recent research that used advanced forensic pathology [11] and computational fluid dynamics simulations [12] indicate that impact trauma is responsible for the vast majority of turbinerelated bat deaths and that barotrauma is likely a minor etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Rollins et al [11] used forensic techniques, including autopsy and radiology, and found that while the barotrauma hypothesis could not be dismissed outright, 94% of bat deaths were directly attributable to impact trauma, and only 6% could Printed with a renewable-source ink on paper containing at least 50% wastepaper, including 10% post consumer waste.…”
Section: Recent Research Calls Into Question the Barotrauma Hypothesismentioning
confidence: 99%
See 1 more Smart Citation